Letter to the Editor: Role of perioperative carcinoembryonic Antigen in guiding adjuvant chemotherapy for colorectal cancer - Wen-Ting Zheng; Guang-Yao Li (World Journal of Clinical Oncology, 2026)
Du et al reported that postoperative carcinoembryonic antigen (CEA) may serve as a cost-effective marker to guide adjuvant chemotherapy in colorectal cancer. Although this study provides clinically relevant findings, several issues need further discussion. First, the retrospective design limits causal interpretation and remains susceptible to selection bias and unmeasured confounding, particularly in non-randomized treatment allocation. Second, the definition and timing of postoperative CEA measurement may influence its predictive value, given its short half-life and potential interference from perioperative factors. Third, the clinical application of CEA-guided treatment requires more rigorous evaluation, including formal interaction testing and consideration of treatment toxicity. Integrating postoperative CEA with emerging biomarkers such as circulating tumor DNA could improve risk stratification. Further prospective studies are needed to validate these findings and clarify their clinical utility.